Geometry of semi-nonholonomic hypercomplexes SNGr(1, 4, 5) in a four-dimensional projective space - Kazimieras Navickis (Lietuvos Matematikos Rinkinys)
In this article the problem of intrinsic normalizations of plane distributions in an four-dimensional projective space is considered.